Computational study of free air-breathing PEM fuel cell Single Cell and Stack. - Sasmito, Agus P.
The operation of proton exchange membrane (PEM) fuel cell for single cells and stacks with free air-breathing open-cathode manifold requires careful thermal, water and gas measurement for optimal performance. Here, the cathode channel design and orientation of the cell/stack in the gravitational field are essential due to presence of buoyancy-driven flow. To study the impact of these effects, a three-dimensional two-phase flow model accounting for conservation equations of mass, momentum, species and energy are solved in ambient and cell/stack with additional conservation of charge, agglomerate catalyst layer-sub-model and a phenomenological membrane model is considered inside the cell/stack. Three computational units are selected for the cathode flow field design based on the fuel cell length for a single cell : (a) 2.5 cm; (b) 5 cm; and (c) 10 cm. The fourth case (d) considers a stack comprising of twelve cells. Furthermore, the orientation of the fuel cell/stack is studied for the case of horizontal, vertical and a 45 degree alignment. Results show that there is a strong correlation between cathode channel design, alignment, thermal management and the cell/stack performance. For the shortest cell (case a), sufficient oxygen can reach the catalyst layer on the cathode side. The longer the cell to height ratio becomes, the higher the degree of oxygen starvation. For the stack (case d), the temperature needs to be carefully monitored and adjusted to the operating conditions of the stack to avoid overheating.
Keywords: Buoyancy